Albizia lebbeck Seed Protein Hydrolysates Inhibit α-Amylase and α-Glucosidase in vitro - Ekun, Oluwafemi; Ojajuni, Adedoyinsola David; Laoye, Tomilola Grace; Amusan, Deborah Motunrayo; Bakinde, Adedolapo Adeola; Ekun, Racheal Gift; Ajewole, Deborah Oluwafunbi; Ashogbon, Precious Yemi; Akinsulu, Opeyemi Glory (Hasanuddin University, 2024)
Albizia lebbeck seeds have been found to contain a high proportion of proteins, which on hydrolysis have yielded hydrolysates which contained bioactive peptides that possessed antioxidant activities in earlier studies. Hence, this study investigated the potentials of these hydrolysates in inhibiting two carbohydrate – hydrolyzing enzymes, α-amylase and α-glucosidase. Albizia lebbeck seed proteins were hydrolyzed using the proteinases trypsin, chymotrypsin and papain. The hydrolysates obtained were evaluated for their inhibitory effects against α-amylase and α-glucosidase. The results revealed that Albizia lebbeck seed proteins were most susceptible to chymotrypsin hydrolysis (degree of hydrolysis of 62.43±1.685%) when compared to those of trypsin and papain. However, hydrolysates obtained from papain hydrolysis exhibited the highest inhibitory activities against α-amylase (70.453±1.619%) whereas tryptic digests inhibited α-glucosidase better than chymotrypsin and papain hydrolysates (55.354±0.808%). The result also suggest that proteinase specificity influenced the relative enzyme-inhibitory activities of the resulting hydrolysates, in terms of the nature of peptides released. The study concludes that Albizia lebbeck seed proteins, on proteolysis with appropriate enzymes, possess potentially therapeutic peptides which can be further characterized towards the development of provide peptide-based alternatives in the management of diabetes mellitus.